Comparison of the phenolic profiles and physicochemical properties of different varieties of thermally processed canned lychee pulp. Issue 12 (13th February 2020) - Wang, Zhineng; Wu, Guangxu; Shu, Bin; Huang, Fei; Dong, Lihong; Zhang, Ruifen; Su, Dongxiao
Abstract : Lychee pulp is rich in phenolics and has a variety of biological activities. Abstract : Lychee pulp is rich in phenolics and has a variety of biological activities. However, the changes in the phenolic profile under heat treatment are unknown. The effect of the heat treatment temperature on commercial varieties ( Guiwei and Nuomici ) of canned lychee was investigated by comparing samples that were either unheated (UH), underwent 70 °C heat treatment (HT70) or underwent 121 °C heat treatment (HT121) and then were stored at room temperature. The results showed that the total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of the UH, HT70 and HT121 samples were significantly decreased after storage at room temperature for 9 d, 13 d and 25 d, respectively. However, the TPC, TFC and antioxidant activity of HT121 canned lychee were still significantly higher than those of the UH and HT70 samples. However, the texture characteristics of the HT121 samples were worse than those of the UH and HT70 samples, and the color of the canned lychee was darker after the HT121 treatment. Nine individual phenolic compounds were detected in the canned lychee by HPLC-DAD. The gallic acid content was increased after HT121 treatment. In particular, (−)-gallocatechin was generated by HT121 thermal processing. However, after storage at room temperature for 9 d, the contents of (−)-gallocatechin in canned Guiwei and Nuomici were decreased by 96.27% and 94.04%, respectively, and (−)-gallocatechin disappeared after 25 d. In summary, the phenolic contents and antioxidant activity of canned lychee are increased by high-temperature treatment.